PELAKSANAAN PEMBELAJARAN ANSAMBEL MUSIK DI KELAS XI IPS 2 SMA NEGERI 1 PADANG SAGO - Muhammad Ikhsan Mardian; Yensharti Yensharti; Esy Maestro (FBS Universitas Negeri Padang, 2017)
ABSTRACTThis research aims to find out and describe the implementation of music ensamble learning at class of XI IPS 2 at SMAN 1 Padang Sago. The design of the research was qualitative using descriptive data analysis. The primary instrument was the research himself while the secondary ones were student’ observation sheets and lesson plans. Data were obtained from library study, interview, and documentation. The objects were 24 students of class XI IPS 2 of the school. The research result shows that the learning process runs well and is based on the syllabus as well lessons plans. The students were required to be able perform the song Cinta Untuk Mama* within a group. The lessons plans were design for 4 meetings. Each meeting included materials for the students by applying the lecturing, demonstration, and exercise methods. The students were divided into three groups. One of them was pointed as the conductor. At the final meeting, the students were able to perform the song in a harmonious tempo and dynamics written in the song’s patition.Keywords: Learning Implementation, Music Ensamble